The midvastus surgical approach in total knee arthroplasty - Maestro, A. (Springer-Verlag, 2000)
We report a study of 2 surgical approaches to the knee in 42 consecutive patients undergoing a total arthroplasty. They were divided into 2 groups. In Group 1 (n=17) the knee was exposed through classic medial parapatellar arthrotomy and in Group 2 (n=25) the knee was approached through the fibers of the medial vastus. Preoperative assessment did not reveal any statistical differences between the groups, and blood loss, operation time, biochemistry values and radiographic evaluation were also similar. However, a higher number of lateral releases, a loss of knee extension and a reduced range of motion were significantly associated with classical parapatellar arthrotomy. As the number of operative or postoperative complications was not increased, we recommend the mid-vastus approach for total knee arthroplasty.